Development of Infrastructure and Changes in the Social Space of Kharkiv at the Turn of the 19th – 20th Centuries - Khovtura, Anastasiia Sergiivna (The Journal of V. N. Karazin Kharkiv National University. Series History, 2020)
The article explored the impact of urban infrastructure on the social space of Kharkov in the late 19th – early 20th centuries. Kharkiv municipality began to implement large-scale infrastructure projects that contributed to solving urgent sanitary-epidemiological and social problems from the 1870s. The first significant technological component of the infrastructure was water supply. Telephone communications, electric lighting, sewage, horse and electric trams started to function in Kharkiv at that time. Networks of medical, educational and cultural institutions were widely developed. The publication clarified the role of certain actors in the creation and maintenance of infrastructure elements. In particular, thanks to Kharkiv municipality declared the basics of collective safety, occupational health, social ecology and formed communicative relations of infrastructure institutions with consumers. Attention is also focused on the role of Kharkiv philanthropic organizations and expert groups, which contributed to the awareness of citizens of such an ethical principle as social responsibility. In the article considered changes in the material substrate of the social space of Kharkiv. It is noted that although the center of the city was the zone of “prestige”, however, the localization of the components of the city infrastructure gradually expanded, which became one of the important features of the modernization of the social space of the city. Networks of hospitals and educational institutions covered remote Kharkiv areas. Public transport and stationary trading establishments become part of the everyday practices of residents of the city’s environs. It is concluded that the development of infrastructure not only changed the physical appearance of the city, but also transformed social practices and the symbolic coding of social space.